Ontogenic changes in coloration of rare deepwater Richardson’s ray Bathyraja richardsoni (Arhynchobatidae, Rajiformes, Chondrichthyes) - Orlov, Alexei M. 1960- (Russian journal of developmental biology)
The features of the coloration of the dorsal and ventral surfaces of the rare deep-sea Richardson's ray Bathyraja richardsoni (Arhynchobatidae) in the length range from 14 to 146 cm have been studied and its ontogenetic changes have been traced. New data on the coloration of embryos, immature, maturing, and sexually mature individuals are presented. It is shown that variations in the coloration of the dorsal surface are insignificant, while the coloration of the ventral surface can vary significantly. The data obtained can be used in taxonomic and population studies, in the development of keys for species identification, in the preparation of faunal overviews and field guides, to facilitate understanding the features of coloration and its changes in deep-sea animals living in permanent darkness, and to expand knowledge about certain aspects of macro- and microevolution of deep-sea skates.